Análise da relação entre o excesso de confiança de gestores de empresas brasileiras e a estratégia empresarial - Andrade, Jefferson Pereira de (2019)
The overconfidence of managers, leaders and entrepreneurs comprises a bias that may constitute a possible threat to business strategy, since it can influence the decision-making process, underestimating the risks involved in making decisions. The objective of the present study was to analyze the influence of the overconfidence of managers of brazilian companies in the business strategy. Six strategic dimensions were studied (working capital and production cycle, advertising intensity, research and development intensity, expenditure structure, investment in fixed assets and capital structure), which were related to three different indicators of overconfidence (the general confidence index, the overconfidence index and the dummy entrepreneur manager), through multiple regression analysis estimated by Ordinary Least Squares (OLS). Panel data were used unbalanced regarding 244 public companies, for the period 2011-2017, through which the following results were obtained: the indicators showed that not all the managers studied are overconfident (according to the general confidence index this total reaches 85,9%, while the entrepreneur manager variable indicates 54,1%). Among the analyzed dimensions, only the advertising intensity, the P&D intensity and the expenditure structure have not been shown to be influenced by the manager's overconfidence. With regard to working capital management and capital structure, the results have shown a negative influence of managers' overconfidence, implying that optimistic managers have greater difficulty in promoting greater inventory turnover, mainly impacting the capital structure. Regarding investment in fixed assets, as well as strategic change, the results show a positive influence of the cognitive bias of the overconfidence, and it is verified that the confident managers tend to expose the company to the greater risk caused by the uncertainty coming through change and with investments returns.